Surgical, Radiographic, and Patient-Related Risk Factors for Proximal Junctional Kyphosis: A Meta-Analysis. Issue 1 (February 2019) - Kim, Jun S.; Phan, Kevin; Cheung, Zoe B.; Lee, Nam; Vargas, Luilly; Arvind, Varun; Merrill, Robert K.; Gidumal, Sunder; Di Capua, John; Overley, Samuel; Dowdell, James; Cho, Samuel K.
Study Design: Meta-analysis. Objective: Proximal junctional kyphosis (PJK) is a complication of surgical management for adult spinal deformity with a multifactorial etiology. Many risk factors are controversial and their relative importance are not fully understood. We aimed to identify the surgical, radiographic, and patient-related risk factors associated with PJK and proximal junctional failure (PJF). Methods: A systematic literature search was performed using PubMed, Cochrane Database of Systematic Reviews, and EMBASE. The inclusion criteria included prospective randomized control trials and prospective/retrospective cohort studies of adult patients with radiographic evidence of PJK, which was defined as a proximal junctional sagittal Cobb angle ≥10° and at least 10° greater than the preoperative measurement. Studies required a minimum of 10 patients and 12 months of follow-up. Results: A total of 14 unique studies, including 1908 patients were included. The pooled analysis showed significant differences between the PJK and non-PJK groups in age (weighted mean difference [WMD] −3.80; P = .03), prevalence of osteopenia/osteoporosis (odds ratio [OR] 1.99; P = .0004), preoperative sagittal vertical axis (SVA) (WMD −17.52; P = .02), preoperative lumbar lordosis (LL) (WMD −1.22; P = .002), pedicle screw instrumentation at the upper instrumented vertebra (UIV) (OR 1.67; P = .02), change in SVA (WMD −11.87; P = .01), fusion to sacrum/pelvis/ilium (OR 2.14; P < .00 001), change in LL (WMD −5.61; P = .01), and postoperative SVA (WMD −7.79; P = .008). Conclusions: Our meta-analysis suggests that age, osteopenia/osteoporosis, high preoperative SVA, high postoperative SVA, low preoperative LL, use of pedicle screws at the UIV, SVA change/correction, LL change/correction, and fusion to sacrum/pelvis/iliac region are risk factors for PJK.